Liquid lithium cylindrical battery
By using a combination of sulfide solid electrolyte tube and liquid lithium metal negative electrode solution in liquid lithium cylindrical batteries, combined with the optimized ceramic sintering process and protective layer settings, the problems of low conductivity and safety hazards of traditional batteries are solved, and more efficient , safer battery performance.
Patent Information
- Application Number
- CN202510006912.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional problems such as low conductivity in room temperature, high preparation cost, high maintenance cost and high safety hazards, especially the side reaction between liquid lithium metal negative electrode and solid electrolyte.
The design of liquid lithium cylindrical batteries includes sulfide solid electrolyte tubes, rod-shaped positive electrode current collectors with positive electrode active substances on the surface, and liquid lithium metal negative electrode solutions. By optimizing the ceramic sintering process and the setting of protective layer, the grain boundaries are reduced and denser and form a stable conductive adhesive layer and a protective layer.
It significantly improves the cycle stability and safety of the battery, enhances the overall performance of the battery, including the improvement of energy output rate and response sensitivity, reduces the cost of electrolyte tubes, and ensures the stability and reliability of battery quality.
Smart Images

Figure CN119400971A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and in particular relates to a liquid lithium cylindrical battery. Background Art
[0002] With the increasing popularity of renewable energy and the continued growth of electricity demand, the importance of grid energy storage technology has become increasingly prominent. It plays an indispensable role in balancing power supply and demand and enhancing the stability and flexibility of the power system. Although cylindrical batteries have made remarkable achievements in the field of grid energy storage, their high operating temperature, high maintenance costs and potential safety hazards cannot be ignored. In view of the rapid response requirements of grid energy storage, the ability of batteries to resist lithium dendrites has become a key consideration.
[0003] Since its introduction in the 1960s, liquid electrode batteries have attracted much attention for their economic and energy storage potential. Their advantages are reflected in significant cost-effectiveness, strong resistance to lithium dendrites, high scalability and high power output. However, the application of liquid metal electrodes faces challenges and requires a high temperature environment that exceeds the melting point of the metal. For example, the melting point of lithium metal is as high as 180 °C. In addition, traditional salt-based electrolytes (such as AlCl 3 -NaCl-LiCl) and oxide solid electrolyte tubular cylindrical batteries all need to maintain their performance under high temperature conditions, which not only increases the cost of manufacturing, operation and maintenance, but also brings safety hazards.
[0004] In contrast, sulfide solid electrolytes exhibit excellent conductivity (about 25 mS / cm) at room temperature and have strong mechanical properties, which effectively ensures the structural stability of the battery. Therefore, sulfides are regarded as key materials for achieving high energy density and enhancing battery safety. Compared with oxide electrolyte tube cylindrical batteries, the superior performance of sulfide electrolytes has laid a solid foundation for the development of sulfide solid electrolyte tube cylindrical batteries. At the same time, the current development of sulfide electrolyte tube cylindrical batteries is still in a blank stage, mainly due to the difficulty of manufacturing sulfide electrolyte tubes and the serious side reaction problems between liquid lithium metal negative electrode solutions and solid electrolytes. Summary of the invention
[0005] The technical solution of the present invention provides a liquid lithium cylindrical battery to address the technical difficulties of traditional low room temperature conductivity, high preparation cost, high maintenance cost and high safety risks.
[0006] The main purposes of the present invention are: 1. To enhance the energy output rate and response sensitivity of battery energy storage technology.
[0007] 2. Improve production efficiency and economic benefits and reduce the cost of electrolyte tubes.
[0008] 3. Improve the ion transmission efficiency of solid electrolytes and at the same time enhance the overall safety protection capabilities of the battery to ensure the stability and reliability of battery quality.
[0009] To achieve the above objectives, the present invention adopts the following technical solutions.
[0010] A liquid lithium cylindrical battery, comprising a solid electrolyte tube, a positive electrode rod, a liquid negative electrode and a shell; the solid electrolyte tube is a sulfide solid electrolyte tube; the positive electrode rod is inserted into the solid electrolyte tube; the liquid negative electrode is a liquid lithium metal negative electrode solution; the liquid negative electrode and the solid electrolyte tube with the positive electrode rod inserted are assembled in the shell, and the sealed shell constitutes the liquid lithium cylindrical battery.
[0011] Preferably, the solid electrolyte tube is formed by ceramicizing and solidifying LPSCl solid electrolyte powder through compaction and / or sintering.
[0012] Preferably, the compaction treatment is as follows: adding electrolyte powder into a rubber mold, rolling and compacting the mold, and then isostatically pressing the mold at a pressure of 540 to 560 kN for 45 to 75 seconds; the sintering treatment is as follows: first, keeping the temperature at 290 to 310 °C for 20 to 30 minutes, then heating the temperature to 470 to 490 °C at a heating rate of 1 °C / min, and keeping the temperature at this temperature for 4 to 8 hours.
[0013] Preferably, the positive electrode rod is a rod-shaped positive electrode current collector with a positive electrode active material loaded on the surface; the positive electrode active material includes an inorganic salt, a polymer and a conductive agent, and the specific loading process is: the inorganic salt, the polymer and the conductive agent are mixed evenly in proportion, added to NMP solvent to dissolve, spin-coated on the rod-shaped positive electrode current collector, baked and dried to obtain the positive electrode rod.
[0014] Preferably, the inorganic salt is lithium iron phosphate; the polymer is PVDF; the conductive agent is Super P; the inorganic salt, polymer and conductive agent are uniformly mixed in a mass ratio of (7.5-8.5): (0.9-1.1): 1; the loading amount of the positive electrode active material on the rod-shaped positive electrode current collector is 0.9-1.1 mg / cm 2 .
[0015] Preferably, the baking is: baking at a temperature of 55-65° C. for 9-11 h; and the drying is: drying at a temperature of 75-85° C. for 5-7 h in a vacuum environment.
[0016] Preferably, before the positive electrode rod is inserted into the solid electrolyte tube, a gelling agent is added to the solid electrolyte tube and evenly coated, and then the positive electrode rod is inserted and allowed to stand for at least 36 hours for gelation, and then the gelling agent forms a conductive adhesion layer.
[0017] Preferably, the specific configuration process of the gelling agent is as follows: tris(2-dioxolane), ethylene glycol dimethyl ether, fluoroethylene carbonate and hexamethyl diisocyanate are uniformly mixed in a volume ratio of (70-80): (22-28): (9-11): 2, and the mixture is rotated and stirred at a temperature of 23-28°C and a rotation speed of 300 r / min until the solution begins to show a gel state.
[0018] Preferably, a protective layer is provided on the outer surface of the solid electrolyte tube; the protective layer is composed of lithium bis(trifluoromethanesulfonyl)imide and polyethylene oxide, wherein the molar ratio O:Li=24):1.
[0019] Preferably, the preparation method of the liquid lithium metal negative electrode solution is: dissolving phenanthrene in a diethylene glycol dimethyl ether solution to prepare a solution with a concentration of 1.8 to 2.2 mol / L, then immersing the lithium filament in the solution, and stirring for 1.5 to 2.5 hours at a temperature of 23 to 28° C. and a rotation speed of 280 to 320 r / min to obtain a liquid lithium metal negative electrode solution.
[0020] In the technical solution of the present invention, the core lies in the use of liquid lithium negative electrode technology, and the difference between the solid electrolyte interface (SEI) film formed on the surface of the liquid lithium negative electrode and the lithium metal negative electrode in the solid electrolyte system is used to solve the interface problem and SEI modification method. It is processed into a cylindrical electrolyte tube by techniques such as particle refinement and isostatic pressing. Subsequently, the electrolyte tube is treated with an optimized ceramic sintering process to reduce grain boundaries and improve density, thereby increasing the critical current density by 33.01% to 4.07 mA / cm². In addition, a protective layer is applied to reduce the side reactions between the liquid lithium metal negative electrode and the sulfide electrolyte tube. The in-situ polymerized gel layer promotes a strong interface contact between the positive electrode active material and the sulfide solid electrolyte tube. The liquid lithium cylindrical battery exhibits stable cycle performance in a wide temperature range of 20 to 55 °C. In the long cycle test, the coulombic efficiency exceeded 99.5% and the energy efficiency exceeded 80%. Even after a freeze-thaw cycle at -70 °C, the mechanical and electrochemical properties of SSET remain stable. These results suggest that adopting sulfide solid electrolytes and liquid lithium could significantly reduce the operating temperature of these batteries and promote their use in stationary energy storage applications.
[0021] The beneficial effects of the present invention are as follows: the solid in the liquid lithium cylindrical battery of the present invention can effectively inhibit the growth of lithium dendrites in the electrolyte, providing a strong guarantee for the cycle stability of the battery. At the same time, the provision of the conductive adhesion layer and the protective layer is also beneficial to improving the safety and reliability of the battery, ensuring good stability between the solid electrolyte tube and the lithium metal, and helping to reduce the growth of lithium dendrites, thereby improving the cycle life and safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the preparation process of sulfide solid electrolyte tube.
[0023] Figure 2 This is the microscopic morphology of the junction between the protective layer and the solid electrolyte.
[0024] Figure 3 The microstructure of the protective layer.
[0025] Figure 4 This is the discharge detection characterization pattern of comparative example 1.
[0026] Figure 5 This is the characterization pattern of the charge and discharge cycle detection of comparative example 2.
[0027] Figure 6 This is the characterization pattern of the charge and discharge cycle detection of comparative example 3.
[0028] Figure 7 This is the characterization pattern of the charge and discharge cycle detection of comparative example 4.
[0029] Figure 8 It is a cycle comparison diagram of commercially available liquid lithium cylindrical batteries and the cylindrical battery of the present invention.
[0030] Fig. 9 This is a long cycle characterization diagram of the cylindrical battery of the present invention at 30°C and 0.3C.
[0031] Fig.10 It is the specific capacity-voltage characteristic curve under different number of cycles in the long cycle process.
[0032] Fig.11 This is a graph of cycle number-specific capacity-Coulombic efficiency-energy efficiency during the freeze-thaw test.
[0033] Fig.12 This is the time-voltage curve during the freeze-thaw test. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below in conjunction with specific embodiments and the accompanying drawings. A person of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by a person of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0035] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0036] Embodiment 1: A liquid lithium cylindrical battery, comprising a solid electrolyte tube, a positive electrode rod, a liquid negative electrode and a shell; the solid electrolyte tube is a sulfide solid electrolyte tube; a protective layer is provided on the outer surface of the solid electrolyte tube; the positive electrode rod is inserted into the solid electrolyte tube; the liquid negative electrode is a liquid lithium metal negative electrode solution; the liquid negative electrode and the solid electrolyte tube with the positive electrode rod inserted are assembled in a shell, and the sealed shell constitutes a liquid lithium cylindrical battery.
[0037] The preparation process of the solid electrolyte tube is as follows Figure 1 As shown, specifically: a-1: Figure 1 The left figure, i.e., as shown in a-1 (a) in the figure, LPSCl sulfide solid electrolyte is used as raw material, added into a rubber mold, and the positive electrode rod is inserted. The mold is rolled back and forth on a horizontal platform for 5 times, and the mold is placed in a plastic bag, vacuumed, and the plastic bag is completely immersed in hydraulic oil, and maintained at a pressure of 540 kN for 75 s. Figure 1 The middle figure, i.e., as shown in a-1 (b) in the figure, isostatic pressing is performed and then demolding and the positive electrode rod is pulled out to obtain a pre-cured tube body. In the above operations, the transfer of the plastic bag to the isostatic pressing equipment cavity and the demolding after the isostatic pressing are all carried out in a glove box.
[0038] a-2: The pre-cured tube body was sealed into a cylindrical ceramic boat, and the temperature was first kept at 290 °C for 30 min in a muffle furnace, and then the temperature was increased to 470 °C at a heating rate of 1 °C / min and kept at this temperature for 6 h. The U-shaped solid electrolyte tube was subjected to secondary sintering to obtain the following: Figure 1 The right picture shows the solid electrolyte tube shown in a-2.
[0039] The preparation process of the positive electrode rod is as follows: the positive electrode active materials lithium iron phosphate, PVDF and Super P are mixed evenly in a mass ratio of 7.5:0.9:1, and mixed with an appropriate amount of NMP solvent to ensure that the positive electrode active materials can be fully dissolved, and the positive electrode active materials are spin-coated to control the loading amount of 0.9 mg / cm on the rod-shaped positive electrode current collector. 2 , baked at 60 °C for 9 h, and dried at 80 °C in a vacuum environment for 5 h to obtain a positive electrode rod.
[0040] The bonding process of inserting the positive electrode rod into the solid electrolyte tube is as follows: tris(2-dioxolane), ethylene glycol dimethyl ether, fluoroethylene carbonate and hexamethyl diisocyanate are uniformly mixed in a volume ratio of 75:25:10:2, and the mixture is rotated and stirred at a temperature of 23°C and a rotation speed of 300 r / min until the solution begins to gel, and the mixture is configured as a gelling agent. A sufficient amount of the gelling agent is added into the solid electrolyte tube, and then the positive electrode rod is inserted, and excess overflowed gel-state material is wiped off. The solid electrolyte tube with the positive electrode rod inserted is vertically stood for 48 hours for gelation so that a stable conductive adhesion layer is formed between the positive electrode rod and the solid electrolyte tube to ensure effective bonding between the two.
[0041] The preparation process of the outer wall protective layer of the solid electrolyte tube is as follows: lithium bis(trifluoromethanesulfonyl)imide and polyethylene oxide are mixed in a molar ratio of O:Li=24:1, and a sufficient amount of 2-amino-3-chloro-1,4-naphthoquinone is added to dissolve to prepare a negative electrode protective solution, the negative electrode protective solution is evenly coated on the outer wall side of the solid electrolyte tube, and the negative electrode protective solution is quickly heated at a temperature of 100°C to remove the external residue of 2-amino-3-chloro-1,4-naphthoquinone, so that a protective layer is formed on the outer wall surface of the solid electrolyte tube.
[0042] After the protective layer is prepared, the SEM characterization of the junction between the solid electrolyte tube and the protective layer is performed. The characterization results are as follows: Figure 2 The SEM characterization results of the protective layer are shown in Figure 3 shown.
[0043] The preparation process of the liquid lithium metal negative electrode solution is as follows: phenanthrene is dissolved in a diethylene glycol dimethyl ether solution to prepare a 2 mol / L solution, then a sufficient amount of lithium filaments are immersed in the solution, stirred for 2.5 h at a temperature of 23° C. and a rotation speed of 280 r / min, and the liquid lithium metal negative electrode solution is obtained by filtering to remove solid impurities.
[0044] Battery assembly: The solid electrolyte tube with the positive electrode rod inserted and processed in the above steps and the prepared liquid lithium metal negative electrode solution are assembled into a 18650 battery shell, and the 18650 battery shell is sealed with silicone rubber to complete the assembly of the full battery.
[0045] The battery prepared in the example was subjected to performance testing, and the specific characterization results are as follows.
[0046] Rate performance test: The battery prepared in the example was subjected to 10 charge and discharge cycles at 0.5 C at temperatures of 20 ℃, 30 ℃, 40 ℃ and 55 ℃, respectively, to test the specific capacity and coulombic efficiency of the battery. The specific characterization results are as follows.
[0047]
[0048] Battery long cycle detection: The battery prepared in the example was subjected to 20 charge and discharge long cycles at 0.3 C at temperatures of 20 ℃, 30 ℃, 40 ℃ and 55 ℃, respectively, to detect the specific capacity of the battery. The specific characterization results are as follows.
[0049]
[0050] Freeze-thaw cycle test: The battery prepared in the embodiment was subjected to charge and discharge cycles at 0.5 C for 32 h at a temperature of 30 ℃, then the battery was frozen at a temperature of -70 ℃ for 6 h, and after thawing, the charge and discharge cycles were carried out at 0.5 C for 64 h at a temperature of 30 ℃, then the battery was frozen at a temperature of -70 ℃ for 6 h, and after thawing, the charge and discharge cycles were carried out at 0.5 C for 32 h at a temperature of 30 ℃. The above operation was regarded as one cycle, and then 10 cycles were performed to detect the specific capacity, coulombic efficiency and energy efficiency of the battery. The specific characterization results are as follows.
[0051]
[0052] The liquid lithium cylindrical battery (i.e., sulfide solid electrolyte tube cylindrical battery) prepared in this example is compared with a commercially available liquid lithium cylindrical battery. The commercially available liquid lithium cylindrical battery and the cylindrical battery of the present invention are similar batteries, and the significant difference is that the electrolyte tube used is an oxide solid electrolyte tube, i.e., an oxide solid electrolyte tube cylindrical battery. The battery is charged and discharged at a rate of 0.1 C at 30 °C, and the specific capacity and coulomb efficiency of the battery are detected. The specific characterization results are as follows: Figure 8 At the same time, the cylindrical battery of the present invention is characterized by 0.3C long cycle under different temperature conditions as shown in Fig. 9 As shown in the figure, according to the characterization results, the cylindrical battery of the present invention has an effectively optimized and improved operating temperature range due to the application of the sulfide solid electrolyte tube, so that it has excellent wide temperature operating characteristics. During the 0.3C long cycle process, the specific capacity-voltage characteristic curves at different cycle numbers are recorded as follows Fig.10As shown, it can be seen that it remains effective and stable during the cycle. In addition, a freeze-thaw test was performed. The number of cycles-specific capacity-Coulomb efficiency-energy efficiency graph during the freeze-thaw test is shown in Fig.11 As shown, the time-voltage curve is Fig.12 As shown, from Fig.11 and Fig.12 It can be seen from the characterization results that the cylindrical battery of the present invention has good temperature resistance and still maintains good performance after the freeze-thaw test.
[0053] Embodiment 2: A liquid lithium cylindrical battery, comprising a solid electrolyte tube, a positive electrode rod, a liquid negative electrode and a shell; the solid electrolyte tube is a sulfide solid electrolyte tube; a protective layer is provided on the outer surface of the solid electrolyte tube; the positive electrode rod is inserted into the solid electrolyte tube; the liquid negative electrode is a liquid lithium metal negative electrode solution; the liquid negative electrode and the solid electrolyte tube with the positive electrode rod inserted are assembled in a shell, and the sealed shell constitutes a liquid lithium cylindrical battery.
[0054] The preparation process of the solid electrolyte tube is as follows: a-1: LPSCl sulfide solid electrolyte is used as a raw material, added into a rubber mold, a positive electrode rod is inserted, the mold as a whole is rolled back and forth on a horizontal platform for 8 times, the mold is placed in a plastic bag, vacuumed, the plastic bag is completely immersed in hydraulic oil, and maintained at a pressure of 550 kN for 60 s. After isostatic pressing, the mold is demolded and the positive electrode rod is extracted to obtain a pre-cured tube body, and in the above operations, the transfer of the plastic bag to the isostatic pressing equipment cavity and the demolding after the isostatic pressing are both carried out in a glove box.
[0055] a-2: The pre-cured tube body is sealed into a cylindrical ceramic boat, and first kept at 300 °C in a muffle furnace for 25 min, then heated to 480 °C at a heating rate of 1 °C / min and kept at this temperature for 6 h. The U-shaped solid electrolyte tube is subjected to secondary sintering to form a solid electrolyte tube.
[0056] The preparation process of the positive electrode rod is as follows: the positive electrode active materials lithium iron phosphate, PVDF and Super P are mixed evenly in a mass ratio of 8:1:1, and mixed with an appropriate amount of NMP solvent to ensure that the positive electrode active materials can be fully dissolved, and the positive electrode active materials are spin-coated to control the loading amount of 1 mg / cm on the rod-shaped positive electrode current collector. 2 , baked at 60 °C for 10 h, and dried at 80 °C in a vacuum environment for 6 h to obtain a positive electrode rod.
[0057] The bonding process of inserting the positive electrode rod into the solid electrolyte tube is as follows: tridioxytungsten, ethylene glycol dimethyl ether, fluoroethylene carbonate and hexamethyl diisocyanate are uniformly mixed in a volume ratio of 75:25:10:2, and the mixture is rotated and stirred at a temperature of 25°C and a rotation speed of 300 r / min until the solution begins to gel, and the mixture is configured as a gelling agent. A sufficient amount of the gelling agent is added into the solid electrolyte tube, and then the positive electrode rod is inserted, and excess overflowed gel-state material is wiped off. The solid electrolyte tube with the positive electrode rod inserted is vertically stood for 48 hours for gelation so that a stable conductive adhesion layer is formed between the positive electrode rod and the solid electrolyte tube to ensure effective bonding between the two.
[0058] The preparation process of the outer wall protective layer of the solid electrolyte tube is as follows: lithium bis(trifluoromethanesulfonyl)imide and polyethylene oxide are mixed in a molar ratio of O:Li=24:1, and a sufficient amount of 2-amino-3-chloro-1,4-naphthoquinone is added to dissolve to prepare a negative electrode protective solution, the negative electrode protective solution is evenly coated on the outer wall side of the solid electrolyte tube, and the negative electrode protective solution is quickly heated at a temperature of 100°C to remove the external residue of 2-amino-3-chloro-1,4-naphthoquinone, so that a protective layer is formed on the outer wall surface of the solid electrolyte tube.
[0059] The preparation process of the liquid lithium metal negative electrode solution is as follows: phenanthrene is dissolved in a diethylene glycol dimethyl ether solution to prepare a 2 mol / L solution, then a sufficient amount of lithium filaments are immersed in the solution, stirred for 2.5 h at a temperature of 23° C. and a rotation speed of 300 r / min, and the liquid lithium metal negative electrode solution is obtained by filtering to remove solid impurities.
[0060] Battery assembly: The solid electrolyte tube with the positive electrode rod inserted and processed in the above steps and the prepared liquid lithium metal negative electrode solution are assembled into a 18650 battery shell, and the 18650 battery shell is sealed with silicone rubber to complete the assembly of the full battery.
[0061] The battery prepared in the example was subjected to the same performance test as in Example 1, and the specific characterization results are as follows.
[0062] Rate performance test: The battery prepared in the example was subjected to 10 charge and discharge cycles at 0.5 C at temperatures of 20 ℃, 30 ℃, 40 ℃ and 55 ℃, respectively, to test the specific capacity and coulombic efficiency of the battery. The specific characterization results are as follows.
[0063]
[0064] Battery long cycle detection: The battery prepared in the example was subjected to 20 charge and discharge long cycles at 0.3 C at temperatures of 20 ℃, 30 ℃, 40 ℃ and 55 ℃, respectively, to detect the specific capacity of the battery. The specific characterization results are as follows.
[0065]
[0066] Freeze-thaw cycle test: The battery prepared in the embodiment was subjected to charge and discharge cycles at 0.5 C for 32 h at a temperature of 30 ℃, then the battery was frozen at a temperature of -70 ℃ for 6 h, and after thawing, the charge and discharge cycles were carried out at 0.5 C for 64 h at a temperature of 30 ℃, then the battery was frozen at a temperature of -70 ℃ for 6 h, and after thawing, the charge and discharge cycles were carried out at 0.5 C for 32 h at a temperature of 30 ℃. The above operation was regarded as one cycle, and then 10 cycles were performed to detect the specific capacity, coulombic efficiency and energy efficiency of the battery. The specific characterization results are as follows.
[0067]
[0068] Embodiment 3: A liquid lithium cylindrical battery, comprising a solid electrolyte tube, a positive electrode rod, a liquid negative electrode and a shell; the solid electrolyte tube is a sulfide solid electrolyte tube; a protective layer is provided on the outer surface of the solid electrolyte tube; the positive electrode rod is inserted into the solid electrolyte tube; the liquid negative electrode is a liquid lithium metal negative electrode solution; the liquid negative electrode and the solid electrolyte tube with the positive electrode rod inserted are assembled in a shell, and the sealed shell constitutes a liquid lithium cylindrical battery.
[0069] The preparation process of the solid electrolyte tube is as follows: a-1: LPSCl sulfide solid electrolyte is used as a raw material, added into a rubber mold, a positive electrode rod is inserted, the mold as a whole is rolled back and forth on a horizontal platform for 10 times, the mold is placed in a plastic bag, vacuumed, the plastic bag is completely immersed in hydraulic oil, and maintained at a pressure of 560 kN for 45 seconds, and after isostatic pressing, the mold is demolded and the positive electrode rod is extracted to obtain a pre-cured tube body, and in the above operations, the transfer of the plastic bag to the isostatic pressing equipment cavity and the demolding after the isostatic pressing are both carried out in a glove box.
[0070] a-2: The pre-cured tube body is sealed into a cylindrical ceramic boat, and first kept at 310 °C in a muffle furnace for 20 min, then heated to 490 °C at a heating rate of 1 °C / min and kept at this temperature for 6 h. The U-shaped solid electrolyte tube is subjected to secondary sintering to form a solid electrolyte tube.
[0071] The preparation process of the positive electrode rod is as follows: the positive electrode active materials lithium iron phosphate, PVDF and Super P are mixed evenly in a mass ratio of 8:1:1, and mixed with an appropriate amount of NMP solvent to ensure that the positive electrode active materials can be fully dissolved, and the positive electrode active materials are spin-coated to control the loading amount of 1 mg / cm on the rod-shaped positive electrode current collector. 2, baked at 60 °C for 11 h, and dried at 80 °C in a vacuum environment for 7 h to obtain a positive electrode rod.
[0072] The bonding process of inserting the positive electrode rod into the solid electrolyte tube is as follows: tris(2-dioxolane), ethylene glycol dimethyl ether, fluoroethylene carbonate and hexamethyl diisocyanate are uniformly mixed in a volume ratio of 75:25:10:2, and the mixture is rotated and stirred at a temperature of 28°C and a rotation speed of 300 r / min until the solution begins to gel, and the mixture is configured as a gelling agent. A sufficient amount of the gelling agent is added into the solid electrolyte tube, and then the positive electrode rod is inserted, and excess overflowed gel-state material is wiped off. The solid electrolyte tube with the positive electrode rod inserted is vertically stood for 48 hours for gelation so that a stable conductive adhesion layer is formed between the positive electrode rod and the solid electrolyte tube to ensure effective bonding between the two.
[0073] The preparation process of the outer wall protective layer of the solid electrolyte tube is as follows: lithium bis(trifluoromethanesulfonyl)imide and polyethylene oxide are mixed in a molar ratio of O:Li=24:1, and a sufficient amount of 2-amino-3-chloro-1,4-naphthoquinone is added to dissolve to prepare a negative electrode protective solution, the negative electrode protective solution is evenly coated on the outer wall side of the solid electrolyte tube, and the negative electrode protective solution is quickly heated at a temperature of 100°C to remove the external residue of 2-amino-3-chloro-1,4-naphthoquinone, so that a protective layer is formed on the outer wall surface of the solid electrolyte tube.
[0074] The preparation process of the liquid lithium metal negative electrode solution is as follows: phenanthrene is dissolved in a diethylene glycol dimethyl ether solution to prepare a 2 mol / L solution, then a sufficient amount of lithium filaments are immersed in the solution, stirred for 2.5 h at a temperature of 23° C. and a rotation speed of 320 r / min, and the liquid lithium metal negative electrode solution is obtained by filtering to remove solid impurities.
[0075] Battery assembly: The solid electrolyte tube with the positive electrode rod inserted and processed in the above steps and the prepared liquid lithium metal negative electrode solution are assembled into a 18650 battery shell, and the 18650 battery shell is sealed with silicone rubber to complete the assembly of the full battery.
[0076] The battery prepared in the example was subjected to the same performance test as in Example 1, and the specific characterization results are as follows.
[0077] Rate performance test: The battery prepared in the example was subjected to 10 charge and discharge cycles at 0.5 C at temperatures of 20 ℃, 30 ℃, 40 ℃ and 55 ℃, respectively, to test the specific capacity and coulombic efficiency of the battery. The specific characterization results are as follows.
[0078]
[0079] Battery long cycle detection: The battery prepared in the example was subjected to 20 charge and discharge long cycles at 0.3 C at temperatures of 20 ℃, 30 ℃, 40 ℃ and 55 ℃, respectively, to detect the specific capacity of the battery. The specific characterization results are as follows.
[0080]
[0081] Freeze-thaw cycle test: The battery prepared in the embodiment was subjected to charge and discharge cycles at 0.5 C for 32 h at a temperature of 30 ℃, then the battery was frozen at a temperature of -70 ℃ for 6 h, and after thawing, the charge and discharge cycles were carried out at 0.5 C for 64 h at a temperature of 30 ℃, then the battery was frozen at a temperature of -70 ℃ for 6 h, and after thawing, the charge and discharge cycles were carried out at 0.5 C for 32 h at a temperature of 30 ℃. The above operation was regarded as one cycle, and then 10 cycles were performed to detect the specific capacity, coulombic efficiency and energy efficiency of the battery. The specific characterization results are as follows.
[0082]
[0083] Comparative Example 1: A liquid lithium cylindrical battery, the specific preparation method is the same as Example 2, only the preparation and coating of the electrode material protective layer are not performed, and the preparation of the liquid lithium cylindrical battery is performed, and the specific operation is as follows: A liquid lithium cylindrical battery, the liquid lithium cylindrical battery comprises a solid electrolyte tube, a positive electrode rod, a liquid negative electrode and a shell; the solid electrolyte tube is a sulfide solid electrolyte tube; the positive electrode rod is inserted into the solid electrolyte tube; the liquid negative electrode is a liquid lithium metal negative electrode solution; the liquid negative electrode and the solid electrolyte tube with the positive electrode rod inserted are assembled in the shell, and the sealed shell constitutes a liquid lithium cylindrical battery.
[0084] The preparation process of the solid electrolyte tube is as follows: a-1: LPSCl sulfide solid electrolyte is used as a raw material, added into a rubber mold, a positive electrode rod is inserted, the mold as a whole is rolled back and forth 8 times on a horizontal platform, the mold is placed in a plastic bag, vacuumed, the plastic bag is completely immersed in hydraulic oil, and maintained at a pressure of 550 kN for 60 s. After isostatic pressing, the mold is demolded and the positive electrode rod is extracted to obtain a pre-cured tube body. In the above operation process, the transfer of the plastic bag to the isostatic pressing equipment cavity and the demolding after the isostatic pressing are carried out in a glove box.
[0085] a-2: The pre-cured tube body is sealed into a cylindrical ceramic boat, and first kept at 300 °C in a muffle furnace for 25 min, then heated to 480 °C at a heating rate of 1 °C / min and kept at this temperature for 6 h. The U-shaped solid electrolyte tube is subjected to secondary sintering to form a solid electrolyte tube.
[0086] The preparation process of the positive electrode rod is as follows: the positive electrode active materials lithium iron phosphate, PVDF and Super P are mixed evenly in a mass ratio of 8:1:1, and mixed with an appropriate amount of NMP solvent to ensure that the positive electrode active materials can be fully dissolved, and the positive electrode active materials are spin-coated on the spin coating to control the loading amount of the positive electrode active materials on the rod-shaped positive electrode current collector to be 1 mg / cm 2 , baked at 60 °C for 10 h, and dried at 80 °C in a vacuum environment for 6 h to obtain a positive electrode rod.
[0087] The bonding process of inserting the positive electrode rod into the solid electrolyte tube is as follows: tridioxytungsten, ethylene glycol dimethyl ether, fluoroethylene carbonate and hexamethyl diisocyanate are uniformly mixed in a volume ratio of 75:25:10:2, and the mixture is rotated and stirred at a temperature of 25°C and a rotation speed of 300 r / min until the solution begins to gel, and the mixture is configured as a gelling agent. A sufficient amount of the gelling agent is added into the solid electrolyte tube, and then the positive electrode rod is inserted, and excess overflowed gel-state material is wiped off. The solid electrolyte tube with the positive electrode rod inserted is vertically stood for 48 hours for gelation so that a stable conductive adhesion layer is formed between the positive electrode rod and the solid electrolyte tube to ensure effective bonding between the two.
[0088] The preparation process of the liquid lithium metal negative electrode solution is as follows: phenanthrene is dissolved in a diethylene glycol dimethyl ether solution to prepare a 2 mol / L solution, then a sufficient amount of lithium filaments are immersed in the solution, stirred for 2.5 h at a temperature of 23° C. and a rotation speed of 300 r / min, and the liquid lithium metal negative electrode solution is obtained by filtering to remove solid impurities.
[0089] Battery assembly: The solid electrolyte tube with the positive electrode rod inserted and processed in the above steps and the prepared liquid lithium metal negative electrode solution are assembled into a 18650 battery shell, and the 18650 battery shell is sealed with silicone rubber to complete the assembly of the full battery.
[0090] The liquid lithium cylindrical battery prepared in the comparative example was tested for charge and discharge performance at a temperature of 30°C and a charge and discharge efficiency of 0.5C. The specific characterization results are as follows: Figure 4 shown.
[0091] analyze Figure 4 The characterization results showed that when there was no protective layer, the sulfide solid electrolyte tubular cylindrical battery had a short circuit phenomenon in the discharge performance. Further analysis of the test results showed that when the internal voltage of the battery was too large, lithium dendrites began to grow at the interface and the surface of the solid electrolyte, causing lithium ions to begin to penetrate into the interface to produce dead lithium, which not only caused a short circuit but also significantly reduced the battery performance.
[0092] Comparative Example 2: A liquid lithium cylindrical battery, the specific preparation method is the same as that of Example 2, except that the secondary sintering of the electrode material is not performed, and the preparation of the liquid lithium cylindrical battery is performed, and the specific operation is as follows: A liquid lithium cylindrical battery, the liquid lithium cylindrical battery comprises a solid electrolyte tube, a positive electrode rod, a liquid negative electrode and a shell; the solid electrolyte tube is a sulfide solid electrolyte tube; a protective layer is provided on the outer surface of the solid electrolyte tube; the positive electrode rod is inserted into the solid electrolyte tube; the liquid negative electrode is a liquid lithium metal negative electrode solution; the liquid negative electrode and the solid electrolyte tube with the positive electrode rod inserted are assembled in a shell, and the sealed shell constitutes a liquid lithium cylindrical battery.
[0093] The preparation process of the solid electrolyte tube is as follows: a-1: LPSCl sulfide solid electrolyte is used as a raw material, added into a rubber mold, a positive electrode rod is inserted, the mold as a whole is rolled back and forth on a horizontal platform for 8 times, the mold is placed in a plastic bag, vacuumed, the plastic bag is completely immersed in hydraulic oil, and maintained at a pressure of 550 kN for 60 s. After isostatic pressing, the mold is demolded and the positive electrode rod is extracted to obtain a pre-cured tube body, and in the above operations, the transfer of the plastic bag to the isostatic pressing equipment cavity and the demolding after the isostatic pressing are both carried out in a glove box.
[0094] a-2: The pre-cured tube body is sealed into a cylindrical ceramic boat, and first kept at 400 °C for 7 h in a muffle furnace to sinter the U-shaped solid electrolyte tube to form a solid electrolyte tube.
[0095] The preparation process of the positive electrode rod is as follows: the positive electrode active materials lithium iron phosphate, PVDF and Super P are mixed evenly in a mass ratio of 8:1:1, and mixed with an appropriate amount of NMP solvent to ensure that the positive electrode active materials can be fully dissolved, and the positive electrode active materials are spin-coated to control the loading amount of 1 mg / cm on the rod-shaped positive electrode current collector. 2 , baked at 60 °C for 10 h, and dried at 80 °C in a vacuum environment for 6 h to obtain a positive electrode rod.
[0096] The bonding process of inserting the positive electrode rod into the solid electrolyte tube is as follows: tridioxytungsten, ethylene glycol dimethyl ether, fluoroethylene carbonate and hexamethyl diisocyanate are uniformly mixed in a volume ratio of 75:25:10:2, and the mixture is rotated and stirred at a temperature of 25°C and a rotation speed of 300 r / min until the solution begins to gel, and the mixture is configured as a gelling agent. A sufficient amount of the gelling agent is added into the solid electrolyte tube, and then the positive electrode rod is inserted, and excess overflowed gel-state material is wiped off. The solid electrolyte tube with the positive electrode rod inserted is vertically stood for 48 hours for gelation so that a stable conductive adhesion layer is formed between the positive electrode rod and the solid electrolyte tube to ensure effective bonding between the two.
[0097] The preparation process of the outer wall protective layer of the solid electrolyte tube is as follows: lithium bis(trifluoromethanesulfonyl)imide and polyethylene oxide are mixed in a molar ratio of O:Li=24:1, and a sufficient amount of 2-amino-3-chloro-1,4-naphthoquinone is added to dissolve to prepare a negative electrode protective solution, the negative electrode protective solution is evenly coated on the outer wall side of the solid electrolyte tube, and the negative electrode protective solution is quickly heated at a temperature of 100°C to remove the external residue of 2-amino-3-chloro-1,4-naphthoquinone, so that a protective layer is formed on the outer wall surface of the solid electrolyte tube.
[0098] The preparation process of the liquid lithium metal negative electrode solution is as follows: phenanthrene is dissolved in a diethylene glycol dimethyl ether solution to prepare a 2 mol / L solution, then a sufficient amount of lithium filaments are immersed in the solution, stirred for 2.5 h at a temperature of 23° C. and a rotation speed of 300 r / min, and the liquid lithium metal negative electrode solution is obtained by filtering to remove solid impurities.
[0099] Battery assembly: The solid electrolyte tube with the positive electrode rod inserted and processed in the above steps and the prepared liquid lithium metal negative electrode solution are assembled into a 18650 battery shell, and the 18650 battery shell is sealed with silicone rubber to complete the assembly of the full battery.
[0100] The liquid lithium cylindrical battery prepared in the comparative example was subjected to charge and discharge cycle performance testing at a temperature of 30°C and a charge and discharge efficiency of 0.5C. The specific characterization results are as follows: Figure 5 shown.
[0101] analyze Figure 5 The characterization results showed that micro-short circuits were very likely to occur when batteries were assembled using solid electrolytes that were not subjected to secondary sintering. Further analysis of the test results showed that due to the presence of cracks and holes inside the solid electrolyte, the anode induced dendrites to form and grow between lithium metal and SEI. The dendrites then penetrated into the SEI, and when the lithium dendrites reached the cathode side, the battery eventually failed.
[0102] Comparative Example 3: A liquid lithium cylindrical battery, the specific preparation method is the same as that of Example 2, only an equal amount of lithium cobalt oxide is used as the positive electrode active material to replace the positive electrode active material in Example 2, and the liquid lithium cylindrical battery is prepared. The specific operation is as follows: A liquid lithium cylindrical battery, the liquid lithium cylindrical battery comprises a solid electrolyte tube, a positive electrode rod, a liquid negative electrode and a shell; the solid electrolyte tube is a sulfide solid electrolyte tube; a protective layer is provided on the outer surface of the solid electrolyte tube; the positive electrode rod is inserted into the solid electrolyte tube; the liquid negative electrode is a liquid lithium metal negative electrode solution; the liquid negative electrode and the solid electrolyte tube with the positive electrode rod inserted are assembled in the shell, and the sealed shell constitutes a liquid lithium cylindrical battery.
[0103] The preparation process of the solid electrolyte tube is as follows: a-1: LPSCl sulfide solid electrolyte is used as a raw material, added into a rubber mold, a positive electrode rod is inserted, the mold as a whole is rolled back and forth on a horizontal platform for 8 times, the mold is placed in a plastic bag, vacuumed, the plastic bag is completely immersed in hydraulic oil, and maintained at a pressure of 550 kN for 60 s. After isostatic pressing, the mold is demolded and the positive electrode rod is extracted to obtain a pre-cured tube body, and in the above operations, the transfer of the plastic bag to the isostatic pressing equipment cavity and the demolding after the isostatic pressing are both carried out in a glove box.
[0104] a-2: The pre-cured tube body is sealed into a cylindrical ceramic boat, and first kept at 300 °C in a muffle furnace for 25 min, then heated to 480 °C at a heating rate of 1 °C / min and kept at this temperature for 6 h. The U-shaped solid electrolyte tube is subjected to secondary sintering to form a solid electrolyte tube.
[0105] The preparation process of the positive electrode rod is as follows: the positive electrode active material lithium cobalt oxide is mixed with an appropriate amount of NMP solvent to ensure that the positive electrode active material can be fully dissolved, and the positive electrode active material is controlled by spin coating to load 1 mg / cm on the rod-shaped positive electrode current collector. 2 , baked at 60 °C for 10 h, and dried at 80 °C in a vacuum environment for 6 h to obtain a positive electrode rod.
[0106] The bonding process of inserting the positive electrode rod into the solid electrolyte tube is as follows: tridioxytungsten, ethylene glycol dimethyl ether, fluoroethylene carbonate and hexamethyl diisocyanate are uniformly mixed in a volume ratio of 75:25:10:2, and the mixture is rotated and stirred at a temperature of 25°C and a rotation speed of 300 r / min until the solution begins to gel, and the mixture is configured as a gelling agent. A sufficient amount of the gelling agent is added into the solid electrolyte tube, and then the positive electrode rod is inserted, and excess overflowed gel-state material is wiped off. The solid electrolyte tube with the positive electrode rod inserted is vertically stood for 48 hours for gelation so that a stable conductive adhesion layer is formed between the positive electrode rod and the solid electrolyte tube to ensure effective bonding between the two.
[0107] The preparation process of the outer wall protective layer of the solid electrolyte tube is as follows: lithium bis(trifluoromethanesulfonyl)imide and polyethylene oxide are mixed in a molar ratio of O:Li=24:1, and a sufficient amount of 2-amino-3-chloro-1,4-naphthoquinone is added to dissolve to prepare a negative electrode protective solution, the negative electrode protective solution is evenly coated on the outer wall side of the solid electrolyte tube, and the negative electrode protective solution is quickly heated at a temperature of 100°C to remove the external residue of 2-amino-3-chloro-1,4-naphthoquinone, so that a protective layer is formed on the outer wall surface of the solid electrolyte tube.
[0108] The preparation process of the liquid lithium metal negative electrode solution is as follows: phenanthrene is dissolved in a diethylene glycol dimethyl ether solution to prepare a 2 mol / L solution, then a sufficient amount of lithium filaments are immersed in the solution, stirred for 2.5 h at a temperature of 23° C. and a rotation speed of 300 r / min, and the liquid lithium metal negative electrode solution is obtained by filtering to remove solid impurities.
[0109] Battery assembly: The solid electrolyte tube with the positive electrode rod inserted and processed in the above steps and the prepared liquid lithium metal negative electrode solution are assembled into a 18650 battery shell, and the 18650 battery shell is sealed with silicone rubber to complete the assembly of the full battery.
[0110] The prepared battery was charged and discharged, and the characterization results are as follows Figure 6 shown.
[0111] analyze Figure 6 The characterization results show that when the voltage of the LCO positive electrode is too high, the conductive adhesion layer cannot withstand a voltage exceeding 3.7 V, causing the interface layer to fail, and thus causing a sharp drop in capacity.
[0112] Comparative Example 4: A liquid lithium cylindrical battery, the specific preparation method is the same as that of Example 2, only an equal amount of titanium disulfide is used as the positive electrode active material to replace the positive electrode active material in Example 2, and the liquid lithium cylindrical battery is prepared. The specific operation is as follows: A liquid lithium cylindrical battery, the liquid lithium cylindrical battery comprises a solid electrolyte tube, a positive electrode rod, a liquid negative electrode and a shell; the solid electrolyte tube is a sulfide solid electrolyte tube; a protective layer is provided on the outer surface of the solid electrolyte tube; the positive electrode rod is inserted into the solid electrolyte tube; the liquid negative electrode is a liquid lithium metal negative electrode solution; the liquid negative electrode and the solid electrolyte tube with the positive electrode rod inserted are assembled in the shell, and the sealed shell constitutes a liquid lithium cylindrical battery.
[0113] The preparation process of the solid electrolyte tube is as follows: a-1: LPSCl sulfide solid electrolyte is used as a raw material, added into a rubber mold, a positive electrode rod is inserted, the mold as a whole is rolled back and forth on a horizontal platform for 8 times, the mold is placed in a plastic bag, vacuumed, the plastic bag is completely immersed in hydraulic oil, and maintained at a pressure of 550 kN for 60 s. After isostatic pressing, the mold is demolded and the positive electrode rod is extracted to obtain a pre-cured tube body, and in the above operations, the transfer of the plastic bag to the isostatic pressing equipment cavity and the demolding after the isostatic pressing are both carried out in a glove box.
[0114] a-2: The pre-cured tube body is sealed into a cylindrical ceramic boat, and first kept at 300 °C in a muffle furnace for 25 min, then heated to 480 °C at a heating rate of 1 °C / min and kept at this temperature for 6 h. The U-shaped solid electrolyte tube is subjected to secondary sintering to form a solid electrolyte tube.
[0115] The preparation process of the positive electrode rod is as follows: the positive electrode active material titanium disulfide is mixed with an appropriate amount of NMP solvent to ensure that the positive electrode active material can be fully dissolved, and the positive electrode active material is controlled by spin coating to load 1 mg / cm on the rod-shaped positive electrode current collector. 2 , baked at 60 °C for 10 h, and dried at 80 °C in a vacuum environment for 6 h to obtain a positive electrode rod.
[0116] The bonding process of inserting the positive electrode rod into the solid electrolyte tube is as follows: tris(2-dioxolane), ethylene glycol dimethyl ether, fluoroethylene carbonate and hexamethyl diisocyanate are uniformly mixed in a volume ratio of 75:25:10:2, and the mixture is rotated and stirred at a temperature of 25°C and a rotation speed of 300 r / min until the solution begins to gel, and the mixture is configured as a gelling agent. A sufficient amount of the gelling agent is added into the solid electrolyte tube, and then the positive electrode rod is inserted, and excess overflowed gel-state material is wiped off. The solid electrolyte tube with the positive electrode rod inserted is vertically stood for 48 hours for gelation so that a stable conductive adhesion layer is formed between the positive electrode rod and the solid electrolyte tube to ensure effective bonding between the two.
[0117] The preparation process of the outer wall protective layer of the solid electrolyte tube is as follows: lithium bis(trifluoromethanesulfonyl)imide and polyethylene oxide are mixed in a molar ratio of O:Li=24:1, and a sufficient amount of 2-amino-3-chloro-1,4-naphthoquinone is added to dissolve to prepare a negative electrode protective solution, the negative electrode protective solution is evenly coated on the outer wall side of the solid electrolyte tube, and the negative electrode protective solution is quickly heated at a temperature of 100°C to remove the external residue of 2-amino-3-chloro-1,4-naphthoquinone, so that a protective layer is formed on the outer wall surface of the solid electrolyte tube.
[0118] The preparation process of the liquid lithium metal negative electrode solution is as follows: phenanthrene is dissolved in a diethylene glycol dimethyl ether solution to prepare a 2 mol / L solution, then a sufficient amount of lithium filaments are immersed in the solution, stirred for 2.5 h at a temperature of 23° C. and a rotation speed of 300 r / min, and the liquid lithium metal negative electrode solution is obtained by filtering to remove solid impurities.
[0119] Battery assembly: The solid electrolyte tube with the positive electrode rod inserted and processed in the above steps and the prepared liquid lithium metal negative electrode solution are assembled into a 18650 battery shell, and the 18650 battery shell is sealed with silicone rubber to complete the assembly of the full battery.
[0120] The prepared battery was charged and discharged, and the characterization results are as follows Figure 7 shown.
[0121] analyze Figure 7The characterization results show that an attempt was made to use a low-voltage lithium-free positive electrode material. However, due to the large volume change of the positive electrode active material during the charge and discharge process, the battery performance gradually decreased.
[0122] The above specific implementations do not constitute a limitation on the protection scope of the present invention. It should be understood by those skilled in the art that various modifications, combinations, sub-combinations and substitutions can be made according to design requirements and other factors. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A liquid lithium cylindrical battery, characterized in that: The liquid lithium cylindrical battery comprises a solid electrolyte tube, a positive electrode rod, a liquid negative electrode and a shell; the solid electrolyte tube is a sulfide solid electrolyte tube; the positive electrode rod is inserted into the solid electrolyte tube; the liquid negative electrode is a liquid lithium metal negative electrode solution; the liquid negative electrode and the solid electrolyte tube with the positive electrode rod inserted are assembled in the shell, and the sealed shell constitutes the liquid lithium cylindrical battery.
2. A liquid lithium cylindrical battery according to claim 1, characterized in that: The solid electrolyte tube is formed by ceramicizing and solidifying LPSCl solid electrolyte powder through compaction and / or sintering.
3. A liquid lithium cylindrical battery according to claim 2, characterized in that: The compaction treatment is as follows: adding electrolyte powder into a rubber mold, rolling and compacting the mold, and then isostatically pressing the mold at a pressure of 540 to 560 kN for 45 to 75 seconds; the sintering treatment is as follows: first, keeping the temperature at 290 to 310 ° C for 20 to 30 minutes, then heating the temperature to 470 to 490 ° C at a heating rate of 1 ° C / min, and keeping the temperature at this temperature for 4 to 8 hours.
4. A liquid lithium cylindrical battery according to claim 1, characterized in that: The positive electrode rod is a rod-shaped positive electrode current collector with a positive electrode active material loaded on the surface; the positive electrode active material includes an inorganic salt, a polymer and a conductive agent. The specific loading process is: the inorganic salt, the polymer and the conductive agent are mixed evenly in proportion, added to an NMP solvent to dissolve, spin-coated on the rod-shaped positive electrode current collector, baked, and dried to obtain the positive electrode rod.
5. A liquid lithium cylindrical battery according to claim 4, characterized in that: The inorganic salt is lithium iron phosphate; the polymer is PVDF; the conductive agent is Super P; the inorganic salt, polymer and conductive agent are uniformly mixed in a mass ratio of (7.5-8.5): (0.9-1.1): 1; the loading amount of the positive electrode active material on the rod-shaped positive electrode current collector is 0.9-1.1 mg / cm 2 .
6. A liquid lithium cylindrical battery according to claim 4, characterized in that: The baking comprises baking at a temperature of 55 to 65° C. for 9 to 11 hours; the drying comprises drying at a temperature of 75 to 85° C. for 5 to 7 hours in a vacuum environment.
7. A liquid lithium cylindrical battery according to claim 1, characterized in that: Before the positive electrode rod is inserted into the solid electrolyte tube, a gelling agent is added to the solid electrolyte tube and evenly coated. After the positive electrode rod is inserted, the gelling agent is allowed to stand for at least 36 hours for gelation to form a conductive adhesion layer.
8. A liquid lithium cylindrical battery according to claim 7, characterized in that: The specific preparation process of the gelling agent is as follows: tris(2-dioxolane), ethylene glycol dimethyl ether, fluoroethylene carbonate and hexamethyl diisocyanate are uniformly mixed in a volume ratio of (70-80): (22-28): (9-11): 2, and the mixture is rotated and stirred at a temperature of 23-28°C and a rotation speed of 300 r / min until the solution begins to show a gel state.
9. A liquid lithium cylindrical battery according to claim 1, characterized in that: A protective layer is provided on the outer surface of the solid electrolyte tube; the protective layer is composed of lithium bis(trifluoromethanesulfonyl)imide and polyethylene oxide, wherein the molar ratio of O:Li is 24:
1.
10. The liquid lithium cylindrical battery according to claim 1, characterized in that: The preparation method of the liquid lithium metal negative electrode solution is as follows: dissolving phenanthrene in a diethylene glycol dimethyl ether solution to prepare a solution with a concentration of 1.8 to 2.2 mol / L, then immersing lithium wire in the solution, and stirring for 1.5 to 2.5 hours at a temperature of 23 to 28° C. and a rotation speed of 280 to 320 r / min to obtain a liquid lithium metal negative electrode solution.
Citation Information
Patent Citations
Method for protecting anode of lithium sulfur battery
CN105140449A
Secondary battery, application and preparation method of negative electrode of secondary battery
CN105742727A
Composite material, preparation method of composite material, and lithium ion battery
CN109755641A
High-temperature liquid metal lithium battery and preparation method thereof
CN110429271A
Novel battery based on sulfide solid-state electrolyte
CN112820935A